Reforming Theological Pedagogy in Christian Religious Education in the Digital Era: A Theological-Didactic Analysis - Paulus Tnunay; Thomas Pentury; Wilson Rajagukguk (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the transformation of theological pedagogy within digital learning environments, focusing on the shift from a transmission-oriented model to a dialogical, reflective, and transformative paradigm. Employing a literature-based approach that engages theories of theological pedagogy, reflective didactics, and digital learning practices, the conceptual synthesis suggests that digital spaces foster new forms of active learner engagement in constructing theological meaning. The analysis identifies three core conceptual transformations: (1) a paradigmatic shift toward participatory learning; (2) a theological reinterpretation of presence and incarnation beyond physical proximity; and (3) the emergence of digital space as a legitimate locus theologicus for experiencing and articulating faith. The discussion further highlights the relevance of Groome’s shared praxis and Klafki’s reflective didactics as foundational frameworks for designing pedagogical models that are both contextually grounded and transformative. Overall, this study contributes to contemporary discussions on theological education by emphasizing the need to reconstruct pedagogical goals, processes, and relational dynamics for the digital age.